Self-regulation workshop and Occupational Performance Coaching with teachers: A pilot study: Étude pilote sur un atelier d'autogestion et des séances d'encadrement du rendement occupationnel à l'intention des enseignants. (April 2016) - Hui, Caroline; Snider, Laurie; Couture, Mélanie
Background: Teachers' occupational role and performance can be undermined when working with students with disruptive classroom behaviours. Purpose: This pilot study aimed to explore the impact of school-based occupational therapy intervention on teachers' classroom management self-efficacy and perceived performance/satisfaction in their management of students with disruptive behaviours. Method: This pilot study used a multiple-case replication study design. A cohort of regular classroom elementary school teachers ( n = 11) participated in a 1-day workshop on sensorimotor strategies for supporting student self-regulation followed by eight individual sessions of Occupational Performance Coaching (OPC). Measurement tools were the Canadian Occupational Performance Measure, Goal Attainment Scaling (GAS), and Teachers' Self-Efficacy Scale–Classroom Management. Findings: Improvement in teachers' perception of performance, satisfaction, and classroom management was seen. GAS showed clinically significant improvement. Improvements were sustained at 7 weeks follow-up. Implications: Preliminary results support the use of sensorimotor education combined with OPC to enable teachers' occupational performance.